Google - The Trailblazer in Employee Satisfaction - Reena Mahapatra Lenka , (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
Google the tech giant is always a source of inspiration and looked upon in awe by most of the similar organizations worldwide. It is a dream come true for any aspiring candidate to be recruited in Google. The main reason for this being optimum employee satisfaction within the organization. Google has understood the fact that in order to have a competitive advantage and be the numero uno tech company in the entire world employees has to be given utmost importance and support so that employees are motivated and satisfied resulting in increased performance and productivity for the Organization. Google with its innovative employee satisfaction method like free food, free gymnasium, career boosting lecture, best salary and compensation, employee entertainment, work flexibility, career development and effective talent management has been able to motivate and satisfy the employees in such a way that employees rarely think of leaving the organization and work tirelessly to make Google tech giant in the world. Many similar organizations like Yahoo and Infosys have been trying to follow the employee satisfaction procedure of Google but without much result. This paper is all about the unique employee satisfaction model followed by Google to gain maximum employee satisfaction which if followed can be a boon for any Organization related to employee satisfaction. This paper is a combination of qualitative and quantitative method.